A Canadian Academic Hospital's Initial MAID Experience: A Health-Care Systems Review. Issue 2 (April 2019) - Ball, Ian M.; Hodge, Brent; Jansen, Sandy; Nickle, Susan; Sibbald, Robert W.
Background: Following the Supreme Court of Canada's Carter Decision, medical assistance in dying (MAID) became possible with individual court orders in February 2016. Subsequently, on June 17, 2016, legislation was passed that eliminated the need for court orders, essentially making physicians the arbiters of these requests. Canadian health-care facilities now face the challenge of addressing this unprecedented patient health-care need. Aim: To describe the manner in which London Health Sciences Center has approached local and regional requests for MAID, including the administration, ethics, privacy, and clinical process. Design: A health-care systems descriptive study. Setting/Participants: Between June 6, 2016, and May 30, 2018, London Health Sciences Center's MAID Internal Resource Committee triaged and referred 260 cases. Ninety-six received the requisite assessments were deemed eligible for and received MAID. Results: The procedure was completed in hospital 59 (61%) times, and 37 (39%) times in the community (either private residence or long-Term Care facility). Nineteen patients did not meet MAID criteria and 63 patients died while awaiting the procedure. The median wait time between first request and referral was 1 day. The median time between referral and the procedure was 12.0 days. The ratio of referrals to completed cases is 96 of 260 (or 37% conversion rate). Conclusion: Our MAID processes, including our committee structure, referral triage process, and physical site have all undergone extensive review and improvement cycles throughout these first 2 years with the aim of ensuring that this procedure is managed in a respectful, confidential, safe, efficient, and patient-centered manner.